East Canadian Light-bellied Brent Geese Branta bernicla hrota wintering at the Havre de Regnéville, France - Burgevin, Philippe (Wildfowl, 2013)
The Havre de Regnéville, France, is a major wintering site for the East Canadian High Arctic Light-bellied Brent Goose Branta bernicla hrota (LBBG) population, which winters mainly on well-known and well-studied sites along the Irish coast. This wintering site has very little eelgrass Zostera sp. available and the geese regularly feed on saltmarshes grazed by sheep. The Conservatoire du littoral is developing several studies to provide a better understanding of why LBBG use this site and to evaluate the possible effects of climate change on its habitat. In particular, the proposed study will analyse a potential conflict of interests between biodiversity and agricultural activity in the area, to provide tools for a better coexistence between the geese and sheep feeding on the saltmarshes.